2021
DOI: 10.17765/2176-9168.2022v15n4e9789
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de cultivares de soja para tolerância aos estresses hídrico e salino durante a fase de estabelecimento da plântula

Abstract: Os estresses hídrico e salino são apontados como os principais fatores abióticos que limitam a germinação e o estabelecimento da cultura de soja. Estudos que visam identificar cultivares com maior tolerância ao estresse hídrico e a salinidade são importantes para a pesquisa agrícola. A pesquisa foi conduzida com a finalidade de avaliar a tolerância de 25 cultivares de soja aos estresses hídrico e salino durante a fase de germinação e crescimento inicial das plântulas. Os estresses hídrico e salino foram induzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…Due to the environmental and soil characteristics of the areas of the Brazilian cerrado where soybean is grown, it is essential to select the genotypes that best suit these characteristics (Cabral, Zuffo, et al, 2022; Crusiol et al, 2021; Jumrani & Bhatia, 2019; Oliveira et al, 2022; Steiner et al, 2019, 2021; Zuffo et al, 2020). In this work, we present a new method to study the importance of morphological variables of genotypes subject to different salt and water stress environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the environmental and soil characteristics of the areas of the Brazilian cerrado where soybean is grown, it is essential to select the genotypes that best suit these characteristics (Cabral, Zuffo, et al, 2022; Crusiol et al, 2021; Jumrani & Bhatia, 2019; Oliveira et al, 2022; Steiner et al, 2019, 2021; Zuffo et al, 2020). In this work, we present a new method to study the importance of morphological variables of genotypes subject to different salt and water stress environments.…”
Section: Discussionmentioning
confidence: 99%
“…Zuffo et al (2020) reported that this index could be used under different stressful environmental conditions to quantify the genotypic stability of soybean cultivars. Cabral, Zuffo, et al (2022) studied 25 soybean cultivars under water and saline stress conditions during germination and initial seedling growth. In this research, three methods were used to evaluate the obtained indices from morphological variables: ranking, hierarchical clustering method and principal component analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Durante o processo de produção das sementes, vários fatores podem afetar sua qualidade, como: condições climáticas extremas, incidência de pragas e patógenos, danos mecânicos e condições de armazenamento [28]. Assim, a germinação das sementes é afetada pela cultivar, devido a diferentes respostas das plantas ao ambiente, em níveis molecular, genético e celular, incluindo alterações fisiológicas, morfológicas e de desenvolvimento, além de alterações nas vias metabólicas [5]. Portanto, as cultivares de soja, principalmente a cultivar UFUS 6901 pode ter sofrido a influência de um ou mais desses fatores ambientais, o que resultou em menor taxa de germinação.…”
Section: Germinação De Sementesunclassified
“…Sementes de alta qualidade podem emergir com maior rapidez e produzir campos mais uniformes, o que é relevante especialmente em ambientes desfavoráveis. Com isso, há maior garantia no estabelecimento da cultura, obtendo-se uma população de plantas desejada e crescimento homogêneo [5].…”
Section: Introductionunclassified